Improving Teacher Digitalization Skills Through Training and Assistance in Creating Virtual Laboratories Assisted by Macromedia Flash to Support the Independent Curriculum: Peningkatan Keterampilan Digitalisasi Guru Melalui Pelatihan dan Pendampingan Pembuatan Laboratorium Virtual Berbantuan Macromedia Flash untuk Mendukung Kurikulum Merdeka - Nirmala, Wa; Bahalwan, Farida; Kasliyanto, Kasliyanto; Hulopi, Fauzia; Kolengsusu, Haris (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Merdeka Belajar is an Indonesian government program that aims to improve the quality of education in Indonesia which has the main pillars, namely strengthening literacy, one of which is digital literacy and increasing teacher competence in using technology. Therefore, teachers need to develop and apply technology to conduct school learning. Lack of understanding in using technology is a problem for teachers at SMA Negeri 62 Central Maluku, becoming a significant challenge in efforts to improve the quality of learning at the school. To enhance the quality of learning in schools, especially in science learning, namely by carrying out virtual or digital-based learning activities, one of which is a virtual laboratory. Service activities aim to improve teachers' digitalization skills, supporting the Merdeka curriculum. The activity method is in the form of training and assistance in creating a virtual laboratory, which includes several stages, namely: preparation stage, team coaching stage, training and mentoring stage, and evaluation stage. Based on the pre-test and post-test, digitalization skills/skills in using Macromedia Flash increased by 86%. This can be seen from the very satisfying results of the learning media produced. With limited time, participants could produce simple virtual laboratory learning media with the help of Macromedia Flash. Abstrak Merdeka Belajar adalah program pemerintah Indonesia yang bertujuan untuk meningkatkan mutu pendidikan di Indonesia yang memiliki pilar utama yaitu penguatan literasi salah satunya literasi digital dan peningkatan kompetensi guru dalam penggunaan teknologi. Oleh sebab itu, guru perlu mengembangkan dan menerapkan teknologi dalam melakukan pembelajaran disekolah. Kurangnnya pemahaman dalam menggunakan teknologi merupakan permasalahan guru-guru di SMA Negeri 62 Maluku Tengah menjadi sebuah tantangan yang signifikan dalam upaya meningkatkan kualitas pembelajaran di sekolah tersebut. Untuk meningkatkan kualitas pembelajaran di sekolah khususnya pada pembelajaran IPA yaitu dengan melakukan kegiatan pembelajaran secara virtual atau berbasis digital salah satunya adalah laboratorium virtual. Tujuan kegiatan pengabdian adalah meningkatkan keterampilan digitalisasi guru dalam mendukung kurikulum Merdeka. Metode kegiatan berupa pelatihan dan pendampingan pembuatan laboratorium virtual yang meliputi beberapa tahap yaitu: tahap persiapan, tahap coaching tim, tahap pelatihan dan pendampingan, tahap evaluasi. Berdasarkan pree test dan post test, keterampilan digitalisasi/keterampilan penggunaan macromedia flash meningkat sebesar 86%. Hal ini dapat dilihat dari hasil media pembelajaran yang dihasilkan sangat memuaskan. Dengan waktu yang terbatas, peserta mampu menghasilkan media pembelajaran laboratorium virtual berbantuan macromedia flash yang sederhana.